Photosynthesis, water use, and root viability under water stress as affected by expression of SAG12-ipt controlling cytokinin synthesis in Agrostis stolonifera - Merewitz, Emily B (Journal of experimental botany, 2011)
Water stress reduces endogenous cytokinin (CK) content and may inhibit CK production. Maintenance of endogenous CK levels by genetic transformation with ipt in leaves and roots undergoing senescence may promote stress tolerance. This study was designed to determine the physiological effects of ipt expression on immature and mature leaves and in roots for plants exposed to different levels of water stress for creeping bentgrass (Agrostis stolonifera). Plants containing the ipt gene, encoding the enzyme adenine isopentenyl phosphotransferase for CK synthesis ligated to a senescence-activated promoter (SAG12), and wild-type 'Penncross' (WT) were grown hydroponically in a growth chamber and exposed to water stress by weekly additions of polyethylene glycol 8000 to reduce the growing solution osmotic potential from -0.05 to -0.3, -0.5, -0.7, -1.0, and -1.4 MPa. Immature and mature leaves and roots of SAG12-ipt creeping bentgrass were evaluated for ipt expression, CK content, leaf relative water content (RWC), chlorophyll content (Chl), photochemical efficiency (F(v)F(m)), osmotic adjustment (OA), photosynthesis rate (Pn), stomatal conductance (g(s)), transpiration (E), water use efficiency (WUE), carbon isotope discrimination (Δ), and root viability. Expression of ipt was detected in all plant parts and a higher CK content, primarily in the form of isopentyladenine (iPa), was found in SAG12-ipt plants but not in the WT plants under water stress. Immature leaves exhibited higher iPa and OA at all treatment levels. Mature leaves of SAG12-ipt plants maintained higher OA, Pn, Chl, WUE, and Δ, whereas g(s) and E were relatively unaffected compared to the WT. Roots of SAG12-ipt plants had higher levels of iPa and greater root viability than the WT. The results demonstrate that expression of ipt enhanced the tolerance of creeping bentgrass to water stress, which could be attributed to the positive effects on osmotic adjustment, efficient water use, and maintaining higher photosynthetic rate primarily for mature leaves, as well as increased root viability